2005
DOI: 10.1016/j.micromeso.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobisation of mesoporous γ-Al2O3 with organochlorosilanes—efficiency and structure

Abstract: Hydrophobisation of mesoporous -Al2O3 with organochlorosilanes-efficiency and structure Castricum, H.L.; Sah, A.; Mittelmeijer-Hazeleger, M.C.; ten Elshof, J.E. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…Organo-silane products are used in surface modification to provide a convenient and stable means to create a hydrophobic ceramic surface and tailor the effective pore size (Miller and Koros 1990;Caro et al 1998;Castricum et al 2005;Javaid et al 2001;Abidi et al 2006;Hyun et al 1996;Leger et al 1996;Randon and Paterson 1997). Alkyl, chloro-alkyl, or fluoro-alkyl silanes of varying carbon chain lengths can be used to provide chemical affinity, to improve the separation performance, and to provide a specific degree of pore size reduction (Javaid et al 2001).…”
Section: Grafting Processmentioning
confidence: 99%
“…Organo-silane products are used in surface modification to provide a convenient and stable means to create a hydrophobic ceramic surface and tailor the effective pore size (Miller and Koros 1990;Caro et al 1998;Castricum et al 2005;Javaid et al 2001;Abidi et al 2006;Hyun et al 1996;Leger et al 1996;Randon and Paterson 1997). Alkyl, chloro-alkyl, or fluoro-alkyl silanes of varying carbon chain lengths can be used to provide chemical affinity, to improve the separation performance, and to provide a specific degree of pore size reduction (Javaid et al 2001).…”
Section: Grafting Processmentioning
confidence: 99%
“…Grafting polymers on ceramic membranes offers the opportunity to tailor and manipulate interfacial properties, while retaining the mechanical strength and geometry of the supported ceramic material. Several types of molecules can be used for modification of inorganic materials, for instance phosphate derivatives [4][5][6], chlorosilanes and alkoxysilanes [2,3,7,8], polysiloxanes [9] and Grignard reactants [10]. The strategy employed in this paper, is grafting with polydimethylsiloxanes.…”
Section: Introductionmentioning
confidence: 99%
“…Because no solvents are used in the gas or vapour phase deposition method, the presence of water can be excluded. Still modification of metal oxides with different kinds of organosilanes is mostly performed by solution phase methods [4][5][6][7][16][17][18][19][20][21][22][23]27,28]. In literature some studies are reported on gas-solid reactions of silanes onto metal oxide surfaces [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work on -Al 2 O 3 powders [22] we demonstrated that both monofunctional ((CH 3 ) 3 SiCl) and a difunctional ((CH 3 ) 2 SiCl 2 ) methylchlorosilanes can be effective for bulk modification of mesoporous materials with pore sizes around 4-5 nm. Steric hindrance limits the use of silanes with long organic tails to materials with much larger pore sizes.…”
Section: Introductionmentioning
confidence: 89%